EXPLORING THE SATISFACTION OF ECOTOURISM IN PROTECTED NATURAL AREAS - Mauricio CARVACHE-FRANCO; Orly CARVACHE-FRANCO; Wilmer CARVACHE-FRANCO (Geo Journal of Tourism and Geosites, 2020)
Enhancing the tourists’ visit to protected areas is vital for destinations that have natural and cultural wealth. The objective of this study is to analyze the aspects of satisfaction with ecotourism in three important protected areas. The empirical study was conducted in situ at Morro Mangroves Wildlife Refuge, Santay Island National Recreation Area and Samanes National Recreation Area in Ecuador. Hence, with the use of quantitative correlational techniques, 382 questionnaires were analyzed. Findings reveal high satisfaction and loyalty in ecotourism. The most valued factors in the satisfaction were the tranquility, conservation of the natural and monumental heritage, the humane treatment received and the access to the infrastructure. In ecotourism, general satisfaction influences the intentions of returning, recommending and expressing positive things about the destination. These findings will contribute to the development of efficient marketing plans in destinations related to ecotourism.